Philosophy of Religion: Taking Leave of the Abstract Domain - Philip Wilson (Religions)
John Cottingham argues that traditional university modules in the philosophy of religion take us into a ‘very abstract domain that is often far removed from religion as it actually operates in the life of the believer’. This paper makes four moves based on Cottingham. First, it argues that the application of Ludwig Wittgenstein’s methods supports and facilitates a shift to the anthropological in the philosophy of religion (as evidenced in the work of Mikel Burley). Second, literature is examined as a tool for doing the philosophy of religion, following Danielle Moyal-Sharrock’s notion of the literary text as surveyable representation. Three works are investigated, namely Silence by Shūshaku Endō, The Brothers Karamazov by Fyodor Dostoevsky, and the Gospel of John. It is argued that, far from being merely illustrative of religion, story is (in its widest sense) constitutive of belief. Third, it is shown how Wittgenstein’s remarks on mysticism in the Tractatus Logico-Philosophicus can be read as a transmutation of literary writing that creates a non-abstract mysticism of the world. Wittgenstein’s remarks are placed in dialogue with Angelus Silesius’s poetry and Leo Tolstoy’s The Gospel in Brief. Fourth, the relevance of Wittgenstein to the current debate on cultural Christianity is brought out. Philosophers of religion must take leave of the abstract, if only to return to it and to view it differently. Wittgenstein’s thought is too important to ignore in this venture.